Conscious sedation/monitored anesthesia care versus general anesthesia in patients undergoing transcatheter aortic valve replacement: A meta-analysis - Hung, Kuo-Chuan; Chen, Jen-Yin; Hsing, Chung-Hsi; Chu, Chin-Chen; Lin, Yao-Tsung; Pang, Yu-Li; Teng, I-Chia; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Cardiovascular Medicine, 2023)
Background: To compare the merits and safety between conscious sedation/monitored anesthesia (CS/MAC) and general anesthesia (GA) for patients receiving transcatheter aortic valve replacement (TAVR). Measurements: Databases including EMBASE, MEDLINE, and the Cochrane Library databases were searched from inception to October 2022 to identify studies investigating the impact of CS/MAC on peri-procedural and prognostic outcomes compared to those with GA. The primary outcome was the association of CS/MAC with the risk of 30-day mortality, while secondary outcomes included the risks of adverse peri-procedural (e.g., vasopressor/inotropic support) and post-procedural (e.g., stroke) outcomes. Subgroup analysis was performed based on study design [i.e., cohort vs. matched cohort/randomized controlled trials (RCTs)] Main Results: Twenty-four studies (observational studies, n=22; RCTs, n=2) involving 141965 patients were analyzed. Pooled results revealed lower risks of 30-day mortality [odd ratios (OR)=0.66, p<0.00001, 139731 patients, certainty of evidence (COE): low], one-year mortality (OR=0.72, p=0.001, 4827 patients, COE: very low), major bleeding (OR=0.61, p=0.01, 6888 patients, COE: very low), acute kidney injury (OR=0.71, p=0.01, 7155 patients, COE: very low), vasopressor/inotropic support (OR=0.25, p<0.00001, 133438 patients, COE: very low), shorter procedure time (MD=-12.27 minutes, p=0.0006, 17694 patients, COE: very low), intensive care unit stay (mean difference(MD)=-7.53 hours p=0.04, 7589 patients, COE: very low), and hospital stay [MD=-0.84 days, p<0.00001, 19019 patients, COE: very low) in patients receiving CS/MAC compared to those undergoing GA without significant differences in procedure success rate, risks of cardiac-vascular complications (e.g., myocardial infarction) and stroke. The pooled conversion rate was 3.1%. Results from matched cohort/RCTs suggested an association of CS/MAC use with a shorter procedural time and hospital stay, and a lower risk of vasopressor/inotropic support. Conclusions: Compared with GA, our results demonstrated that the use of CS/MAC may be feasible and safe in patients receiving TAVR. However, more evidence is needed to support our findings because of our inclusion of mostly retrospective studies.